2019
DOI: 10.1038/s41746-019-0135-8
|View full text |Cite
|
Sign up to set email alerts
|

Adopting machine learning to automatically identify candidate patients for corneal refractive surgery

Abstract: Recently, it has become more important to screen candidates that undergo corneal refractive surgery to prevent complications. Until now, there is still no definitive screening method to confront the possibility of a misdiagnosis. We evaluate the possibilities of machine learning as a clinical decision support to determine the suitability to corneal refractive surgery. A machine learning architecture was built with the aim of identifying candidates combining the large multi-instrument data from patients and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…It is also possible that this is an area where well‐designed artificial intelligence (AI) may be able to provide some decision support to clinicians. AI technologies are being developed to assist in interpretation of clinical tests like radiology, and to replace traditional clinical algorithms (Hov et al, ; Lynn, ; Yoo et al, ). AI offers the potential to analyze complicated components of a patient's case which clinicians may not be able to interpret, and it is reasonable to believe that these programs will soon be able to provide guidance on which patients may benefit from genetic testing, and what actions should be taken based on GS results.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that this is an area where well‐designed artificial intelligence (AI) may be able to provide some decision support to clinicians. AI technologies are being developed to assist in interpretation of clinical tests like radiology, and to replace traditional clinical algorithms (Hov et al, ; Lynn, ; Yoo et al, ). AI offers the potential to analyze complicated components of a patient's case which clinicians may not be able to interpret, and it is reasonable to believe that these programs will soon be able to provide guidance on which patients may benefit from genetic testing, and what actions should be taken based on GS results.…”
Section: Discussionmentioning
confidence: 99%
“…Study subjects included 18,480 healthy Korean patients who intended to undergo refractive surgery at the B&VIIT Eye Center from January 2016 to June 2018. 5 The retrospective study adhered to the tenets of the Declaration of Helsinki. The study protocol was approved by the Institutional Review Board of the Korean National Institute for Bioethics Policy (KoNIBP, 2018-2734-001).…”
Section: Methodsmentioning
confidence: 99%
“… 3 , 4 A previous study indicated that the machine learning technique can evaluate medical information to identify candidates for corneal refractive surgery. 5 However, previous machine learning models are considered as a black box and lack an explicit knowledge representation. 6 They are unable to provide reasoning and explanations on a decision in a manner similar to human experts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, artificial intelligence-based techniques have revolutionized many fields ranging from medical data analyses to intricate image classification [7,8]. These contributions are not limited to research as deep learning techniques and highly efficient hardware are being introduced in clinics as well [9].…”
Section: Introductionmentioning
confidence: 99%